Estimated plasma volume status as a prognostic indicator in myocardial infarction and heart failure: insights from the MIMIC-IV database - Luo, Bin; Ma, Zheng; Zhang, Guoyong; Jiang, Xue; Guo, Caixia (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMyocardial infarction (MI) complicated by heart failure (HF) is a common and severe clinical condition associated with poor outcomes. Estimated plasma volume status (ePVS), a marker of congestion derived from hemoglobin and hematocrit, has shown promise in predicting outcomes in various cardiovascular diseases. This study aimed to investigate the relationship between ePVS and both short-term and long-term prognosis in patients with MI complicated by HF.MethodsA retrospective cohort study was conducted using data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, including 3,238 patients with MI complicated by HF. Patients were stratified into quartiles based on ePVS values. The primary outcomes were in-hospital mortality, 180-day mortality, and 1-year mortality. Kaplan–Meier curves, multivariate Cox regression analysis, and subgroup analyses were performed to assess the relationship between ePVS and outcomes.ResultsKaplan–Meier analysis showed significant differences in survival rates across ePVS quartiles for all outcomes (P < 0.001). Multivariate logistic regression analysis revealed that patients in the highest quartile of ePVS (Q4 vs. Q1) had an independently increased risk of in-hospital mortality (OR 1.58, 95% CI 1.16–2.13, P = 0.003). Cox regression analysis further demonstrated that higher ePVS (Q4 vs. Q1) was associated with an increased risk of 180-day mortality (HR 1.45, 95% CI 1.19–1.75, P < 0.001) and 1-year mortality (HR 1.51, 95% CI 1.27–1.80, P < 0.001). Both Kaplan–Meier survival curves and restricted cubic spline models confirmed a positive association between ePVS and long-term mortality risks.The association between ePVS and long-term outcomes was stronger than for in-hospital mortality. Subgroup analyses revealed that the relationship between ePVS and long-term mortality was more pronounced in patients with systolic blood pressure below 140 mmHg, lower LODS and OASIS scores, and those without hemorrhagic disorders or anemia (P for interaction <0.05).ConclusionePVS was an independent predictor of both short-term and long-term mortality in patients with MI complicated by HF. Its prognostic value was particularly significant for long-term outcomes, suggesting its potential utility in risk stratification and guiding treatment strategies for this high-risk population.